2020
DOI: 10.1016/j.annonc.2020.08.1610
|View full text |Cite
|
Sign up to set email alerts
|

1296P BLU-945, a highly potent and selective 4th generation EGFR TKI for the treatment of EGFR T790M/C797S resistant NSCLC

Abstract: Conclusions:In the FLAURA China study, median OS was extended by 7.4 months in the osimertinib arm vs comparator EGFR-TKI arm in the first-line treatment of pts with EGFRm advanced NSCLC, consistent with the global population where osimertinib extended OS by 6.8 months. Safety data were comparable with the global population.Clinical trial identification: NCT02296125. Editorial acknowledgement:We thank Natalie Griffiths, PhD, from iMed Comms, who provided medical writing support funded by AstraZeneca.Legal enti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…To do so, plasma genotyping needs to be considered during the treatment, as well as tumor biopsy at progression to detect the ARM to the EGFR/BRAF/MEK pathway co-inhibition. Interestingly, an ARM to EGFR/BRAF/MEK pathway co-inhibition, with osimertinib as the EGFR TKI, may be the EGFR C797S mutation, which is potentially targetable with the fourth generation EGFR TKI BLU-945 [9,10,25,43].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…To do so, plasma genotyping needs to be considered during the treatment, as well as tumor biopsy at progression to detect the ARM to the EGFR/BRAF/MEK pathway co-inhibition. Interestingly, an ARM to EGFR/BRAF/MEK pathway co-inhibition, with osimertinib as the EGFR TKI, may be the EGFR C797S mutation, which is potentially targetable with the fourth generation EGFR TKI BLU-945 [9,10,25,43].…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“… 162 , 163 BLU-945 is another fourth-generation EGFR-TKI targeting the T790M/C797S mutation reported in ESCO. 164 In vitro data suggested that BLU-945 achieved robust inhibition of Ex19del/T790M/C797S and L858R/T790M/C797S triple mutation, rather than EGFR WT . Cell-derived xenograft and patient-derived xenograft models consistently showed that single treatment with BLU-945 or coadministration with osimertinib/gefitinib significantly blocked the progression of tumors with the Ex19del/T790M/C797S mutation.…”
Section: Exploration Of Next-generation Egfr-tkismentioning
confidence: 98%
“… 162 L858R/T790M/C797S BBT-176 Bridge Bio Ex19del/T790M/C797S NA phase I Pharmabiz 163 L858R/T790M/C797S BLU-945 Blueprint Medicines Ex19del/T790M/C797S NA pre-clinical Schalm et al. 164 L858R/T790M/C797S Brigatinib a TAKEDA Pharma Ex19del/T790M/C797S reversible FDA approved Uchibori et al. 103 L858R/T790M/C797S ATP competitive a Multiple-target inhibitor.…”
Section: Exploration Of Next-generation Egfr-tkismentioning
confidence: 99%
“…The 4th generation of EGFR TKIs, including EAI045 and BLU-945, are currently being studied to overcome C797S which is the most significant on-target resistance mechanism to osimertinib [ 28 ]. EAI045 is the first allosteric inhibitor that targets T790M and C797S EGFR mutations.…”
Section: Introductionmentioning
confidence: 99%
“…It has shown efficacy in combination with cetuximab in mouse models [ 29 ]. BLU-945 is another fourth-generation EGFR TKI that potently inhibits triple-mutant EGFR that harbors either activated L858R or exon 19 deletion mutations, plus acquired T790M and C797S mutations [ 28 ]. A Phase I/II, open-label, first-in-human (FIH) study NCT04862780 is recruiting to evaluate the safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD), and anticancer activity of BLU-945 in EGFR-mutated NSCLC who have previously received at least 1 prior EGFR-targeted TKI including those with C797S mutation.…”
Section: Introductionmentioning
confidence: 99%